2018
DOI: 10.3122/jabfm.2018.04.170222
|View full text |Cite
|
Sign up to set email alerts
|

Screenings during Well-Child Visits in Primary Care: A Quality Improvement Study

Abstract: Background: Early Periodic Screening, Diagnosis, and Treatment visits are designed to address physical, mental, and developmental health of children enrolled in Medicaid.Methods: We conducted a mixed methods intervention by using a quality improvement theory. We assessed preintervention and postintervention screening rates of development, anemia, lead, oral health, vision and hearing, interventions for improvement, and barriers for the well-child visits at an academic family medicine clinic. For quantitative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Nurses are highly valued and trusted by the public (Rubin et al., 2017). This emphasizes the need to increase good and open communication with the parents to convince them to adhere to recommendations contained in referrals (Chung et al., 2006), market the importance of screening tests and their value for the future life of the child (Wakai et al., 2018) and, most importantly, recognize families with difficulties and help them deal with their challenges (Perry et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Nurses are highly valued and trusted by the public (Rubin et al., 2017). This emphasizes the need to increase good and open communication with the parents to convince them to adhere to recommendations contained in referrals (Chung et al., 2006), market the importance of screening tests and their value for the future life of the child (Wakai et al., 2018) and, most importantly, recognize families with difficulties and help them deal with their challenges (Perry et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Findings could support HCs in improving blood lead testing by screening those who required a blood lead test (eg, Medicaid covered patients) and educating parents/guardians about lead exposure at early wellchild visit in primary care settings. 22 Previous research has identified barriers to childhood lead screening, such as cost, lack of insurance, and absence of symptoms. 23 In addition, inadequate parental adherence to physician-ordered screening and physician noncompliance with screening recommendations are barriers to childhood lead screening.…”
Section: Discussionmentioning
confidence: 99%
“…The scale of the QI project can vary from a single clinical site to a large multispecialty group as the above example used. For example, Wakai et al 25 conducted a QI project in a single site but included an intervention. Focused on improvement of periodic assessments, they identified and addressed barriers and threats to the project’s success.…”
Section: Discussionmentioning
confidence: 99%